Hubungan Pengetahuan Remaja Tentang HIV/AIDS Dengan Sikap Pencegahan HIV/AIDS Di SMA Negeri 1 Gurah Kabupaten Kediri - Arika Indah Setyarini; Ira Titisari; Putri Adi Ramadhania (Akademi Keperawatan Dharma Husada Kediri, 2016)
Almost every week the prostitution in Gurah are visited by teenager from junior, senior high school and college student. This things caused the knowledge about HIV/AIDS is still less so made the attitude is worst too. The purpose of this study was to analyze the correlation between knowledge of teenager about HIV / AIDS with HIV/AIDS prevention attitude of HIV / AIDS in State 1 Senior High School Gurah, District Kediri. This study used cross sectional method. The number of population is 198 and samples was 67 according to the inclusion and exclusion criteria used stratified proportional random sampling and questionnaire and analyzed using Spearman rank correlation test. The analyzed result used Spearman test with an error level of 5% (0,05) used the formula ρ, ρ = 0,62, because simple random sampling technique. Data was collected using a sample are 67 so it’s calculated used t formula with result t = 6,36. Then the t compared to the t table and got the result t value (6,36) > t table (1,996), which means Ho is rejected and it means there is a correlation between knowledge of teenager about HIV / AIDS with HIV/AIDS prevention attitude of HIV / AIDS in State 1 Senior High School Gurah, District Kediri. The conclusion is good knowledge will influence the good attitude too. So that, suggested that teenagers should more added knowledge about HIV/AIDS so the knowledge will be better. Keywords : HIV/AIDS, Knowledge, Teenager, Attitude